A critical evaluation of validity and utility of translational imaging in pain and analgesia: Utilizing functional imaging to enhance the process. (January 2018) - Upadhyay, Jaymin; Geber, Christian; Hargreaves, Richard; Birklein, Frank; Borsook, David
Highlights: Most clinical measures informing on chronic pain are non-translatable to the preclinical setting. Parallels in CNS function are observed between preclinical & clinical pain states. Measuring CNS function may further the comprehension of pain and pain phenotypes. A translational neuroimaging assay in pain research may facilitate discovery of new analgesic. Abstract: Assessing clinical pain and metrics related to function or quality of life predominantly relies on patient reported subjective measures. These outcome measures are generally not applicable to the preclinical setting where early signs pointing to analgesic value of a therapy are sought, thus introducing difficulties in animal to human translation in pain research. Evaluating brain function in patients and respective animal model(s) has the potential to characterize mechanisms associated with pain or pain-related phenotypes and thereby provide a means of laboratory to clinic translation. This review summarizes the progress made towards understanding of brain function in clinical and preclinical pain states elucidated using an imaging approach as well as the current level of validity of translational pain imaging. We hypothesize that neuroimaging can describe the central representation of pain or pain phenotypes and yields a basis for the development and selection of clinically relevant animal assays. This approach may increase the probability of finding meaningful new analgesics that can help satisfy the significant unmet medical needs of patients.